Carnival in Tel Aviv Purim and the Celebration of Urban Zionism - Shoham, Hizky (Israel: Society, Culture, and History, 2014)
The Tel Aviv annual Purim celebrations were the largest public events in British Palestine, and they played a key role in the development of the urban Jewish experience in the Promised Land. Carnival in Tel-Aviv presents a historical-anthropological analysis of this mass public event and explores the ethnographic dimension of Zionism. This study sheds new light on the ideological world of urban Zionism, the capitalistic aspects of Zionist culture, and the urban nature of the Zionist project, which sought to create a nation of warriors and farmers, but in fact nationalized the urban space and constructed it as its main public sphere.